El fenómeno de la responsabilidad social empresarial (2013)
This article will briefly outline the concept and the current regulations on the issue of Corporate Social Responsibility (CSR) globally. Also presents an initial idea of CSR and shows companies as a necessary strategy for economic, social and environmental sustainability approach. Submit for Corporate Social Responsibility and the process as the result of a comprehensive chain of actions involving all members of interest groups